Effect of Soret and temperature dependent viscosity on thermohaline convection in a ferrofluid saturating a porous medium - Sekar, R.; Raju, Kuppusamy (Zielona Góra: Uniwersytet Zielonogórski)
Soret driven ferrothermoconvective instability in multi-component fluids has a wide range of applications in heat and mass transfer. This paper deals with the theoretical investigation of the effect of temperature dependent viscosity on a Soret driven ferrothermohaline convection heated from below and salted from above subjected to a transverse uniform magnetic field in the presence of a porous medium. The Brinkman model is used in the study. It is found that the stationary mode of instability is preferred.
Keywords: ferroconvection; porous medium; Soret effect; multi-component system; Brinkman model; temperature dependent viscosity; Galerkin technique